Carborane RAFT agents as tunable and functional molecular probes for polymer materials. Issue 13 (26th February 2019) - Messina, Marco S.; Graefe, Christian T.; Chong, Paul; Ebrahim, Omar M.; Pathuri, Ramya S.; Bernier, Nicholas A.; Mills, Harrison A.; Rheingold, Arnold L.; Frontiera, Renee R.; Maynard, Heather D.; Spokoyny, Alexander M.
Abstract : Carborane RAFT agents are introduced as tunable multi-purpose tools acting as 1 H NMR spectroscopic handles, Raman probes, and recognition units. Abstract : Functional handles appended to polymer chain ends are important tools often used as spectroscopic probes for determining polymer structure, affinity labels, and as reactive handles for the conjugation of functional payloads. An easily tunable molecular handle able to carry out multiple functions simultaneously would be of significant use at the polymer, materials, and biology interface. Here, we report the development of carborane-containing chain transfer agents (CTAs, commonly referred to as RAFT agents) which are used in reversible addition–fragmentation chain transfer (RAFT) polymerization. These carborane RAFT agents establish control over polymerization processes leading to monodisperse ( Đ = 1.03–1.15) polymers made from N -isopropylacrylamide, styrene, 4-chlorostyrene, and methyl acrylate monomers. The tunable nature of the carborane-based scaffold appended on the polymer chain end serves as a general 1 H NMR spectroscopic handle, which can be used to elucidate polymer molecular weight via end-group analysis. Isothermal titration calorimetry (ITC) measurements show that synthesized carborane terminated polymers exhibit strong binding to β-cyclodextrin with an affinity ( K a ) of 9.37 × 10 4 M −1, thereby demonstrating its potential use as an affinity label. Additionally, we show that the free B–H vertices on the carborane RAFT agents exhibit a Raman vibrational signal at ∼2549 cm −1, a Raman-silent region for biological milieu, indicating its potential utility as an innate Raman active probe. The reported carborane RAFT agents bolster the expanding toolbox of molecular probes and serve as tunable platforms for incorporating additional and complementary handles for tailoring chain-end functionality and facilitating polymer analysis.